Perfect PR - Maitland, Iain. (London : International Thomson Business Press, 1999)
Planning PR activities. Issuing press releases. Managing interviews. Organizing press conferences. Running your PR campaign.
Keywords: Management; Public relations; Public relations -- Management; Public relations